STRATEGI PENGEMBANGAN USAHA PEMBIBITAN SAPI POTONG PADA P4S CAHAYA PURNAMA DESA TEPIAN BARU KECAMATAN BENGALON KABUPATEN KUTAI TIMUR - Joni Ariansyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The purpose of this study was to analyze the development strategy of breeding beef cattle in P4S Cahaya Purnama Bengalon East Kutai. This study was conducted in May 2016. The research was conducted at the Center for Agricultural Training, Rural, and Governmental (P4S) Cahaya Purnama Bengalon. The research data were collected in the form of primary and secondary data. Besides, it also conducted in-depth interviews with several informants (Mantra, 2008). The method used is qualitative survey and analyzed descriptively. In addition, this study also use the method of literature related to supporting data. In developing P4S, Ministry of Agriculture of the Republic of Indonesia has issued guidelines for the growth and development of P4S (MOA RI, 2007). In these guidelines has been described in detail how the goals established by monitoring P4S. P4S New Light has been directing its activities on the concept of integrated agriculture and animal husbandry. Activities already underway that is how the activities of cattle breeding which produce manure and used as fertilizer, will then be used to fertilize crops and plantation there. SIDA strategy can also be applied to the activities of breeding cattle in P4S Cahaya Purnama. SIDA strategies can be unified with the concept of agribusiness. In East Kutai, agribusiness breeding and fattening beef cattle can be the right choice. Enterprises beef cattle breeding activity in the P4S Cahaya Purnama already running and developed quite well. The concept of agribusiness strategy that incorporates the agricultural and plantation sectors are very worthy recommended for development P4S Cahaya Purnama.